2010
DOI: 10.1073/pnas.1009199108
|View full text |Cite
|
Sign up to set email alerts
|

Defects in succinate dehydrogenase in gastrointestinal stromal tumors lacking KIT and PDGFRA mutations

Abstract: Carney-Stratakis syndrome, an inherited condition predisposing affected individuals to gastrointestinal stromal tumor (GIST) and paraganglioma, is caused by germline mutations in succinate dehydrogenase (SDH) subunits B, C, or D, leading to dysfunction of complex II of the electron transport chain. We evaluated the role of defective cellular respiration in sporadic GIST lacking mutations in KIT or PDGFRA (WT). Thirty-four patients with WT GIST without a personal or family history of paraganglioma were tested f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
486
2
17

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 560 publications
(515 citation statements)
references
References 42 publications
10
486
2
17
Order By: Relevance
“…[5][6][7] More recently, these tumors have been subcategorized into genetically defined subgroups, including tumors with activating mutations in BRAF, [8][9][10] loss-offunction mutations in NF1, or loss-of-function mutations in components of the inner mitochondrial membrane Krebs cycle enzyme complex succinate dehydrogenase (SDH). 11,12 This latter group of tumors has been designated 'SDH-deficient GIST'. 13,14 The observed distinctions in molecular genotype have important implications for the biological properties of the tumor, as well as sensitivity to targeted therapies.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7] More recently, these tumors have been subcategorized into genetically defined subgroups, including tumors with activating mutations in BRAF, [8][9][10] loss-offunction mutations in NF1, or loss-of-function mutations in components of the inner mitochondrial membrane Krebs cycle enzyme complex succinate dehydrogenase (SDH). 11,12 This latter group of tumors has been designated 'SDH-deficient GIST'. 13,14 The observed distinctions in molecular genotype have important implications for the biological properties of the tumor, as well as sensitivity to targeted therapies.…”
mentioning
confidence: 99%
“…13,15 The SDH complex is comprised of or modified by proteins encoded by SDHA, SDHB, SDHC, SDHD, and SDHAF2. 16 Germline mutations in these genes have been identified in patients with paraganglioma, [17][18][19][20][21][22] renal cell carcinoma, 23,24 and GIST, 11,12 as well as syndromes of multiple tumor types. 11,13 In GIST, alterations in SDH have most commonly been reported in SDHB, but also have been found in SDHC, SDHD, and, recently, SDHA.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in all four SDH genes have been demonstrated in gastric 'wild-type' GISTs. [13][14][15][16][17] Recent studies have identified SDHA as the most commonly mutated subunit, with SDHA mutations found in approximately 30% of SDHdeficient GISTs. [18][19][20][21] However, around 40% of SDH-deficient GISTs lack demonstrable mutations in an SDH subunit gene.…”
mentioning
confidence: 99%
“…Since the initial discovery of SDHD mutations in 2000, mutations in SDHB and SDHC , and more recently, SDHA and SDHAF2 (encoding the protein responsible for FAD incorporation into SDH) have been identified with the same syndrome 47, 48, 49, 60. These mutations are found as heterozygous germline mutations, which means that loss of protein function and neoplastic transformation develops as a result of loss of heterozygosity, resulting in the complete loss of enzyme function by a second ‘hit.’61 Inactivating mutations of SDH subunits have since been reportedly associated with other tumor types including gastrointestinal stromal tumors,62 renal cell carcinoma,63, 64 and neuroblastoma 65, 66. Interestingly, mutations of SDHB predispose to a more malignant and aggressive form of paraganglioma than those of the other subunits, despite the apparent similarities in both functional and downstream phenotypic consequences of this mutation.…”
Section: Mutations Of Mitochondrial (And Associated) Metabolic Enzymementioning
confidence: 99%